Improving financial education to the poor at the bottom-of-pyramid: the role of social finance vis a vis financial institutions - Arsyianti, Laily Dwi; Kassim, Salina (2015)
This paper aims to explore the role of Islamic social finance and financial institutions in contributing towards improving financial inclusion through financial education among the poor. While there have been a lot of efforts undertaken by financial institutions, especially microfinance institutions, to achieve the financial inclusion agenda, the financial inclusion programs would normally require high operational costs which many financial institutions would consider them as not commercially viable. The costs then are transferred back to the customers, resulting in the financing/credit cost higher than commercial financial institutions. As a result, incidences of bankruptcy increase when the cost of credit is higher. Thus, financial education is essential for average family in managing their day to day financial resources. While financial institutions keep busy with financial inclusion agenda and trying to find the best way without disturbing their core business agenda, Islam offers social finance institution (amil and nadzir) as the solution to this problem.